THE EVOLUTION OF FEDERALISM IN ANCIENT WORLD - Sanjay Khan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research paper delves into the evolution of federalism in the ancient world, tracing its origins and development across various civilizations. By examining various city-states, leagues, empires, and kingdoms of the ancient world, the study highlights the diverse manifestations and adaptations of federal principles in early societies.The analysis reveals that federalism, characterized by a division of power between central authorities and constituent units, was a recurring governance model, facilitating political stability and economic cooperation while preserving local autonomy. In Mesopotamia, early city-states and the Akkadian Empire exemplified nascent federal structures, while the biblical confederation of Israel's tribes offered a unique tribal form of federalism. The Greek Achaean League and the Persian Achaemenid Empire further demonstrated the effectiveness of federal systems in complex and expansive territories.In India the governance of the Mahajanapadas, Maurya, and Gupta Empires reflected federalist elements, balancing centralized authority with regional autonomy. The Maya civilization and the Axum kingdom provided additional global perspectives on early federalism.This paper contributes to understanding the foundational role of federalism in shaping ancient political landscapes and its enduring relevance in contemporary governance structures.